White Dwarfs as Dark Matter Collectors: A Study of Elemental Capture Rates - Schaber, Remi (My University, 2025)
This paper investigates the capture of dark matter in white dwarfs, focusing on the interaction between dark matter particles and the ions within the white dwarf’s dense core. The study models the dark matter capture rate using an optically-thin approximation, where each dark matter particle undergoes a single scattering event before either being captured or escaping the white dwarf’s gravitational influence. Key assumptions in the model include a zero core temperature for the white dwarf, a uniform core composition, and the exclusion of multi-scattering events. The paper examines the equations governing the interaction between dark matter and ions within the white dwarf’s core. The results of the calculations indicate that an increase in the mass of the white dwarf, as well as a higher concentration of heavier elements in its core, enhances the dark matter capture rate. The work also highlights potential future refinements, aiming to provide an introduction to the ongoing research to model dark matter interactions in stellar remnants as a potential detection method.
Keywords: dark matter theory; white dwarfs